On the mechanism of carboxylate elimination from carbohydrate monoester-derived radicals - Turner, Julia A.; Zipse, Hendrik; Taylor, Mark S. (Organic & Biomolecular Chemistry, 2024)
A computational study of the mechanism of hydrogen atom transfer-induced carboxylate elimination from monoacylated 1,2-diol groups in pyranosides is presented. A comprehensive analysis of the 1,2-migration, elimination and fragmentation pathways reveals that concerted elimination via a 7-membered, hydrogen-bonded transition state is favored. Relative rates of elimination inferred from an intramolecular competition experiment are consistent with the trends obtained from the calculations.